Pelaksanaan Musharakah di Bank Syariah Mandiri di Jakarta Indonesia - Joni Tamkin Borhan; Paturohman Asrori (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2012)
This article about the operation partnership in the Bank Syariah Mandiri (BSM), Jakarta, Indonesia. The partnership is one of the Islamic banking principles which has been proposed by Islamic economic experts in the Islamic banking operations but in terms of implementation, there are differences in each Islamic bank particularly in the calculation of profits and losses. The methodology of the research is based on interviews and documentation. Both methods were used to gather information and data (primary and secondary) on the implementation of the partnership system and the performance of bank BSM. The method of data analysis is based on the comparative method, that is to compare data from this bank under study. The research has successfully discovered that in general there is in the implementation of the partnership system in these banks from its implementation procedure, the distribution of profits and the termination of the partnership contract.